Assessment of Biodiversity in Food Consumption Studies: A Systematic Review - Medeiros, Maria Fernanda Araújo de; Silva, Stephanie Gomes Bezerra; Teixeira, Carla Djaine; Lima, Severina Carla Vieira Cunha; Marchioni, Dirce Maria; Jacob, Michelle Cristine Medeiros (Frontiers in Nutrition, 2022)
The assessment of food biodiversity has gained importance in nutrition due to the positive association between the diversity of foods consumed and the quality of diets. To date, however, we do not know systematically how food consumption studies address food biodiversity. Our objective with this paper was to characterize how food consumption studies address biodiverse foods, both in terms of (i) new methods capable of overcoming the limitations of existing methods, and (ii) indicators capable of measuring the contribution of biodiversity to nutrition. We conducted a systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), using four databases: Web of Science, Medline/PubMed (via National Library of Medicine), Scopus, and Google Scholar. We selected papers focused on the consumption of biodiverse foods without time constraints. In addition, we assessed the methodological quality of the studies we selected. We reviewed a total of 22 studies, and summarized the methods and indicators most used. We found that some researchers used biodiversity mapping strategies based on ethnographic approaches before the dietary assessment. Regarding dietary assessment tools, retrospective direct methods were the most used by researchers. We list 23 indicators used by the authors, among them the Dietary Species Richness (DSR), used in 18% of the studies. Studies that used biodiversity mapping strategies based on ethnographic approaches before the dietary assessment portrayed the local availability of biodiverse foods more consistently, i.e., presented lists with local edible species satisfactorily identified. We believe researchers in the future can avoid many of the limitations of current methods by ensuring that teams are interprofessional. We emphasize that most of the indicators we summarized are not sensitive enough to biodiversity since they do not measure edible resources at the species level. In this sense, the DSR is promising, because it fills information gaps, especially in the case of wild or neglected species.